Students Perceptions of the Implementation of Guidance and Counseling Field Practices in Schools - Helda Oktafia; Yarmis Syukur (Jurnal Neo Konseling, 2019)
This research is motivated by the fact that there are still students who are not ready to become guidance and counseling teachers, students are used as substitute teachers, there are students who do not get guidance from supervisors or tutor teachers as long as students carry out field counseling and guidance practices in schools. This study aims to describe the perceptions of students towards the implementation of field practice guidance and counseling in schools FIP UNP in Padang Semester July-December 2018.This research is a type of descriptive research using quantitative methods. The population of this research is BK students who have participated in Semester July-December 2018 as many as 98 students and the research sample uses saturated sample technique. Data were analyzed using descriptive statistical techniques.The findings of this study as a whole indicate that students 'perceptions of the implementation of PLBKS are in the good category, and perceptions based on each aspect (1) Students' perceptions based on aspects of preparation for implementation of field practice guidance and counseling in schools are in the good category (54.08%). (2) Student perceptions based on aspects of implementation of field practice guidance and counseling students in Schools are in the good category (62.24%). (3) Student perceptions based on aspects of guiding students implementation of field practice guidance and counseling in schools in Schools are in the good category (46.94%). (4) Student perceptions based on evaluation aspects of implementation of field practice guidance and counseling in schools activities in schools are in the good category (56.12%).Based on the results of the study it is recommended that prospective students take part in field practice guidance and counseling to be able to improve their knowledge, competence, and skills so that they can carry out field practice activities properly.